Pengaruh Latihan Drop Shot Sasaran Tetap dan Berubah terhadap Ketepatan Drop Shot dalam Permainan Bulutangkis Peserta Ekstrakurikuler Bulutangkis di SD - Suroso Suroso; Didi Muhtarom (Lembaga Pengembangan Kinerja Dosen, 2025)
This study was motivated by the low performance of students’ drop shot skills in elementary school badminton extracurricular activities, where the success rate of shots remained low despite regular training. The aim of this research was to analyze the effect of drop shot training using two methods—fixed targets and variable targets—on improving students’ shot accuracy. The study employed an experimental method with a pretest-posttest control group design. The sample consisted of 30 students selected through purposive sampling, with the requirement of having participated in badminton extracurricular activities for at least one year. The participants were divided into two groups: 15 students underwent fixed-target training, and 15 students underwent variable-target training. The training program was implemented over six weeks with a frequency of three sessions per week. The results indicated that both training methods significantly improved students’ drop shot accuracy. However, the variable-target training group showed greater improvement compared to the fixed-target group. This was due to the training variation, which required better concentration, adaptability, and decision-making, making it more similar to real game conditions. These findings highlight the importance of applying varied training methods in developing students’ basic badminton skills. Therefore, this study provides practical implications for coaches to prioritize variable-target training methods in coaching programs to enhance the effectiveness of technical skills, particularly the drop shot.